Passivo ambiental e o setor de exploração de petróleo em terra: abordagem teórica e percepção institucional dos impactos ambientais gerados na atividade - Galdino, Carlos Alberto Bezerra (2006)
The search for a sustainable development is result of the exhaustion of the natural resources of the planet that demands globalizated politics with practical of compatible economic development with the protection of the quality of life for the future generations. This work presents a study on the thematic on the environmental liabilities in the organizations with focus in the industry of the oil and the production of oil in land in the state of Rio Grande do Norte. Some types of environmental liabilities are presented, as well as, some estimates techniques. Moreover, this work presents surveys of some variable that stimulate the organizations to implant technologies of reduction of the impacts in the environment as: the environmental legislation, costs, the main impacts of the production of oil in land. On the basis of the bibliographical research and in the identified variable, it was carried a case study with state and municipal technician that act in the sectors of fiscalization (IBAMA-RN and IDEMA-RN) with the objective to deepen the discussion regarding the impacts of the industry of the oil, the effectiveness of the current law, the performance of the institutions the federal level and how to prevent impacts in the environment. It was observed that the environmental liabilities are a little spread subject in the organizations, perhaps to be unknown and of few theoretical referencees at the national level, regarding to the evaluation techniques. At the same time, absentee in the national politics that conducts the oil exploration